Maritime Cybersecurity: A Guide for Leaders and Managers, Gary C Kessler & Steven D Shepard - Ayesha Abrar (CISS Insight Journal, 2024)
“Maritime Cybersecurity: A Guide for Leaders and Managers,” authored by Gary Kessler and Steven Shepard, dissects crucial cybersecurity aspects over nine chapters, aiming to fortify the maritime domain against evolving threats. Gary is a cybersecurity expert with over forty years of experience specializing in maritime cybersecurity and digital forensics. Steven, the founder of Shepard Communications Group, is a tech industry veteran, author, and educator with thirty-five years of experience and a PhD from the DaVinci Institute.The first chapter offers an in-depth overview of the Maritime Transportation System (MTS), emphasizing its complexity and interdependence across various segments. It underscores the critical need for a holistic cyber defense approach and highlights the diverse stakeholders, significant economic impact, and comprehensive regulatory landscape within the MTS.